2017
DOI: 10.1073/pnas.1713215114
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid polymorphisms constitute distinct clouds of conformational variants in different etiological subtypes of Alzheimer’s disease

Abstract: The molecular architecture of amyloids formed in vivo can be interrogated using luminescent conjugated oligothiophenes (LCOs), a unique class of amyloid dyes. When bound to amyloid, LCOs yield fluorescence emission spectra that reflect the 3D structure of the protein aggregates. Given that synthetic amyloid-β peptide (Aβ) has been shown to adopt distinct structural conformations with different biological activities, we asked whether Aβ can assume structurally and functionally distinct conformations within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
268
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 187 publications
(279 citation statements)
references
References 50 publications
10
268
0
1
Order By: Relevance
“…Spectroscopic changes of the LCO fluorescence response correlated in vitro with concomitant formation of bundled fibrils by AFM and TEM. A recent study of Aβ polymorphism in human samples using the same technology revealed a distribution of spectroscopic signatures from Aβ plaque cores . This strongly suggests that a cloud‐like diversity of Aβ conformations exists within each patient, representative of the variations of Aβ fibrils within a single sample .…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic changes of the LCO fluorescence response correlated in vitro with concomitant formation of bundled fibrils by AFM and TEM. A recent study of Aβ polymorphism in human samples using the same technology revealed a distribution of spectroscopic signatures from Aβ plaque cores . This strongly suggests that a cloud‐like diversity of Aβ conformations exists within each patient, representative of the variations of Aβ fibrils within a single sample .…”
Section: mentioning
confidence: 99%
“…This strongly suggests that a cloud‐like diversity of Aβ conformations exists within each patient, representative of the variations of Aβ fibrils within a single sample . The conformational cloud was weighted towards a certain type of mature or immature fibril distributions depending on the predisposing mutations in the PS1 and APP genes for fAD cases . However, it is not directly known what causes these variations in the qFTAA staining properties; that is, whether they are influenced, for example, by covalent modifications or the presence of nonfibril amyloid plaque components that account for different architectures of the biological deposit .…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…An important indication that variant CJD (the human prionosis that is linked to bovine spongiform encephalopathy) is caused by a novel prion strain was the discovery of atypical lesions termed florid plaques in affected humans (Ironside et al, 2000). As in the case of PrP-prions, Aβ can fold into strain-like variants both in vitro (Petkova et al, 2005; Nilsson et al, 2007; Yagi et al, 2007; Paravastu et al, 2008; Meinhardt et al, 2009; Miller et al, 2010; Kodali et al, 2010; Agopian and Guo, 2012; Spirig et al, 2014; Tycko, 2015; Tycko, 2016) and in vivo (Meyer-Luehmann et al, 2006; Rosen et al, 2010; Rosen et al, 2011; Lu et al, 2013; Heilbronner et al, 2013; Watts et al, 2014; Stohr et al, 2014; Cohen et al, 2015; Condello et al, 2018; Rasmussen et al, 2017). Cerebral Aβ assemblies in humans with AD vary in terms of plaque morphology (Wisniewski et al, 1989; Thal et al, 2006), ligand binding characteristics (Rosen et al, 2010; Condello et al, 2018; Rasmussen et al, 2017), solid-state nuclear magnetic resonance features (Qiang et al, 2017), as well as conformational stability and other biophysical characteristics (Cohen et al, 2015).…”
Section: The Prion-like Properties Of Aggregated Aβmentioning
confidence: 99%
“…Cerebral Aβ assemblies in humans with AD vary in terms of plaque morphology (Wisniewski et al, 1989; Thal et al, 2006), ligand binding characteristics (Rosen et al, 2010; Condello et al, 2018; Rasmussen et al, 2017), solid-state nuclear magnetic resonance features (Qiang et al, 2017), as well as conformational stability and other biophysical characteristics (Cohen et al, 2015). Interestingly, Aβ extracted from the autopsied brains of nondemented elderly subjects exhibits molecular-level features that differ in some ways from AD-derived Aβ (Piccini et al, 2005; Portelius et al, 2015).…”
Section: The Prion-like Properties Of Aggregated Aβmentioning
confidence: 99%